Liason:Wisdom on Social Conflict Management of Lanna - Wanna, Phairin Na (Journal of International Buddhist Studies, 2016)
Human being respects or adheres to something that is the spiritual anchor for feeling warmth, safety and stability in life. There might be reason enough to accept or not, and when it was accepted some the matter then it will be shown whether physical or mental. That regards may call the belief, it is nature that rises to all human beings. Buddhism is called “faith,” he said. When conducting every day for reiteration the confidence. Later, there is the idea to create a symbol for substituting spiritual anchor, then, there was created for various things. The article on “Liaison: Wisdom on social conflict management of Lanna. “ Trying to present their role of liaison that performs as a mediator between the monks and villager in the religious observance ceremony and this is medium in social conflict management of Lanna. To take flexible performance by specifying the rules, appoint layman who used for ordination to be “liaison or grandfather teacher” (a northern language called. Grandfather teacher or teacher). Who never have been the ordination they will not pay respect to be the liaison or grandfather instructors in Lanna society. Therefore, Liaison or grandfather was seen by local villager that monopoly power. In fact, wisdom on social conflict management of Lanna. Because that liaison used to be ordained in Buddhism, they have a better understanding of the Buddha Dharma and to be paid respect in the society. Because of their status or position is significant, there is important since the modern era and applied about the qualification, the roles in line with the changing social, but that still does not change namely; the moral of liaison.